Country-level institutional quality and financial system efficiency: An international evidence - Mohammed Arshad Khan; Muhammad Atif Khan; Muhammad Asif Khan; Hossam Haddad; Nidal Mahmoud Al-Ramahi; Noorjahan Sherfudeen (PLoS ONE, 2023)
The optimum economic outcome of financial system development depends on its level of efficiency. The purpose of this study is to investigate the effect of institutional quality on financial system efficiency. For empirical analysis, we have used a panel dataset of 108 countries from 1996–2020 and employed fixed effect regression and two stages least squares (2SLS) regression methods. The empirical results show that institutional quality has a significant positive effect on financial system efficiency. Particularly all the constituting elements—voice and accountability, political stability and absence of violence, regulatory quality, government effectiveness, rule of law, and control of corruption—of institutional quality are found to have a significant positive impact on financial system efficiency. Moreover, we found that the effect of institutional quality is more pronounced in countries with low-income levels and strong institutional quality. These findings are robust across several robustness tests conducted using additional controls, alternative methodologies, an alternative measure of institutional quality, and financial system efficiency. The results of the study suggest that policy makers should prioritize both enhancing and sustaining institutional quality to promote the efficiency of the financial system, which is crucial for sustainable growth and development.